Hashimoto’s encephalopathy versus catatonia: A diagnostic dilemma - Preeti Singh Dhoat; Amandeep Kaur; Niket Verma; Deepak Jain (Journal of Family Medicine and Primary Care)
Hashimoto’s encephalopathy is a rare life-threatening disease entity with clinical presentation like psychiatric as well as neurological diseases, thus making it a challenging clinical scenario for physicians leading to delay in diagnosis and management of the patient. The incidence overall is under-estimated because of low overall awareness about the disease. Here, we report a 44-year-old female who was being treated for psychiatric disorders because of clinical presentation like catatonia but ultimately was diagnosed with Hashimoto’s encephalopathy and responded very well to steroids.